Serological Evidence of Foot-and-Mouth Disease Infection in Goats in Lao PDR - Singanallur, Nagendrakumar B.; Nampanya, Sonevilay; MacPhillamy, Isabel; Soukvilay, Vilayvanh; Keokhamphet, Chattouphone; Bush, Russell D.; Khounsy, Syseng; Dhand, Navneet K.; Windsor, Peter; Vosloo, Wilna (Frontiers in Veterinary Science, 2020)
Foot and Mouth Disease (FMD) causes significant economic loss in Lao PDR (Laos) and perpetuates the cycle of smallholder poverty through mainly large ruminant productivity losses, increased costs of production and potential limitations to market access for trade in livestock and their products. Goats are emerging as an important livestock species in Laos, and there is an increasing trend in the number of households with goats, often farmed alongside cattle and buffaloes. However, although an FMD susceptible species, very little is known about the role of goats in the epidemiology of the disease in Laos. A cross-sectional seroprevalence study was conducted by detecting antibodies to the non-structural proteins (NSP), an indication of a previous infection, and serotype-specific structural proteins (SP) that could be due to vaccination or infection. The study commenced in late 2017 and sera were collected from goats in 26 villages, located in four northern provinces, three in central Laos and one southern province. For a subset of sera samples, paired oral swab samples were also collected by a simple random sampling method to detect the prevalence of FMD virus infection at the time of collection. The NSP seroprevalence in the provinces of Borkeo and Xayabouli in the north was 42% and 8% respectively and in Khammoune in the centre, it was 20%. In the other five provinces, the seroprevalence was close to zero. Risk factor analysis indicated that age (p = 0.001), sex (p = 0.021) and weight (p = 0.094) were associated with serostatus. We conclude that goats in Laos appear to become infected, but at a lower rate than cattle and buffalo. Continued sero-surveillance for FMD in goats is recommended to improve our understanding of their role in the epidemiology of FMD in the region and to extend support to FMD control decisions, particularly regarding vaccination.